The effect of multidirectional skipping on lay-up ability - Maharani Sanjaya; Iyakrus Iyakrus; Soleh Solahuddin; Wahyu Indra Bayu (Universitas Suryakancana, 2022)
This study aims to determine the effect of jumping rope exercise on the results of the lay-up shoot ability of basketball players at Club Tunas Academy Lahat. This study uses an experimental method with Quasi Experiment Design. This research is quantitative research that uses the research design method